2016
DOI: 10.1002/ps.4366
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of selected boreal fruits and berries to the invasive pestDrosophila suzukii(Diptera: Drosophilidae)

Abstract: Although blueberry growers have experienced severe economic crop losses due to D. suzukii, we have found that blueberries were the least preferred of the fruits tested. This suggests that D. suzukii are largely opportunistic and highlights the importance of fruit phenology in fruit susceptibility. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 32 publications
4
56
0
Order By: Relevance
“…Blueberry and grape are the least fragrant of the tested fruits (Forney, ), which may explain their poor attractiveness when other fruits are present. Drosophila suzukii can oviposit in a wide range of commercial, wild, and ornamental fruits; when other food sources are not available, they can feed on tree sap, honeydew, and host blossoms (Tochen et al, ; Little et al, ). Under laboratory conditions, females survived for almost 21 days and were observed to produce nearly 100 offspring when a honey solution or fruit juice was provided together with an artificial diet for oviposition and development (Kaçar et al, ); the polyphagous nature of the pest may prolong their reproductive period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blueberry and grape are the least fragrant of the tested fruits (Forney, ), which may explain their poor attractiveness when other fruits are present. Drosophila suzukii can oviposit in a wide range of commercial, wild, and ornamental fruits; when other food sources are not available, they can feed on tree sap, honeydew, and host blossoms (Tochen et al, ; Little et al, ). Under laboratory conditions, females survived for almost 21 days and were observed to produce nearly 100 offspring when a honey solution or fruit juice was provided together with an artificial diet for oviposition and development (Kaçar et al, ); the polyphagous nature of the pest may prolong their reproductive period.…”
Section: Discussionmentioning
confidence: 99%
“…Blueberry, cherry, and grape were chosen because they have been reported to suffer considerable damage from D. suzukii in China (Asplen et al, ; Gao et al, ). Strawberry has been listed as a susceptible host abroad (Little et al, ), and apple and banana are often used as oviposition substrates for D. suzukii in the laboratory (Liu et al, ). There have been no reports of any damage or infestation in commercial apples at any location where this pest species occurs (Oregon Department of Agriculture, ), and only damaged or cut apples have been recorded as a host (Kanzawa, ; Dreves et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This causes softening and introduces microbes that shorten shelf life and renders fruit unmarketable [3]. The attack of undamaged ripe fruit along with its wide host range has made it a serious insect pest in many fruit crops such as cherries, raspberries, blackberries, strawberries, and blueberries [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…However, in California, Stewart et al [59] reported that intact peach fruit are unlikely hosts. No doubt, many fruits with hard or hairy skin can be colonized if wounds are available to allow flies to oviposit in the pulp [4,59,60,61].…”
Section: Introductionmentioning
confidence: 99%